Local Economy-Based Ecotourism Development Strategy in Mandailing Natal Community Empowerment Using QSPM - Lubis, Hilma Kholilah; Indah Lestari Nasution, Annio; Daim Harahap, Rahmat (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Mandailing Natal is an area blessed with abundant natural wealth which is also a source of livelihood for the community. empowering nature tourism (ecotourism) as part of a strategy to take advantage of natural wealth in the Mandailing Natal area without damaging the environment is one of the right steps. By utilizing natural resources which are a tourist attraction in the Mandailing Natal district. The purpose of this research is to identify the conditions of ecotourism in Mandailing Natal based on an analysis of Strengths, Weaknesses, Opportunities, and Threat (SWOT) and to find out the best marketing strategy based on alternative marketing strategies that have been obtained using Quantitative Strategic Planning Matrix (QSPM). The research method used is to use the SWOT and QSPM method. The results of the study show that the Ecotourism Conditions in Mandailing Natal based on an analysis of Strengths, Weaknesses, Opportunities, and Threats (SWOT) have great strengths. This is illustrated by the results of the IFAS and EFAS matrix analysis which describe the position of tourist attractions in Mandailing Natal in quadrant 1-2 positions in the SWOT matrix. Quadrant 2 describes Strategic Diversification, namely Tourism Objects in a stable condition but facing a number of tough challenges. Tourist attractions in Mandailing Natal can carry out several strategies to face the big challenges towards goodness, including (1) increasing the facility of cleanliness, (2) prioritizing traders so that the prices offered are with complete police and sizes, (3) utilizing large areas of land for complete the lacking facilities as well as add new innovations supported by the regional government or the tourism office.